Research Progress and Challenges of Shale Oil Reservoir Characteristics - Jia, Linxi (Scientific Journal of Technology, 2025)
This article systematically reviews the latest progress and main challenges in the research of shale oil reservoir characteristics. As an important unconventional oil and gas resource, the study of shale oil reservoir characteristics is of great significance for resource evaluation and development. The article elaborates in detail on the main characteristics of shale oil reservoirs from five aspects: geological features, physical properties, geochemical features, mechanical properties, and development characteristics. It analyzes the key issues and challenges in current research and looks forward to future research directions. The research shows that shale oil reservoirs have typical low porosity and low permeability characteristics, with well-developed nanoscale pores, strong reservoir heterogeneity, and are controlled by multiple geological factors. Future research should focus on multi-scale characterization techniques, digital core technology, and the application of artificial intelligence to promote the efficient development of shale oil.